Exploración sobre la inserción laboral de los intérpretes en el mercado peruano - Argandoña Jara, Andrea (2017)
By the late 40's, the political scenario of the Second World War was mainly characterized by the high necessity to establish diplomatic relationships between the Axis and Allies powers. Within this framework, the Nuremberg trials were the scenario where simultaneous interpreting emerged. Since then, this industry has flourished differently around the world. In Peru, not many studies have been carried out on this professional activity. Therefore, the aim of this paper is to explore the employability process of interpreters in the Peruvian market. The researchers carried out eighteen interviews that explore the testimonies of interpreting graduates from two Peruvian universities: Universidad Ricardo Palma (URP) and Universidad Femenina del Sagrado Corazón (UNIFE). This paper was able to demonstrate that a successful job placement in the interpretation market depends on the appropriate management of soft skills, i.e. the effective use of contact networks, as well as technical and management skills.